2008
DOI: 10.1373/clinchem.2007.101287
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of C-Peptide Measurements

Abstract: BACKGROUND: C-peptide is a marker of insulin secretion in diabetic patients. We assessed within-and between-laboratory imprecision of C-peptide assays and determined whether serum calibrators with values assigned by mass spectrometry could be used to harmonize C-peptide results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 13 publications
(11 reference statements)
2
72
0
1
Order By: Relevance
“…This protocol has also been validated to be suitable for triglycerides and HDL cholesterol (15 ) and for creatinine (16 ). The C37A protocol has not been validated to produce samples that are commutable with patient samples for other analytes but represents the best available approach and has been used to prepare single-donor serum samples and pools for several investigations of the trueness of measurement procedures for several analytes (17)(18)(19)(20)(21). Thienpont et al found that processing of serum (e.g., sterile filtration, storage before aliquoting and freezing) may disturb the equilibrium between free and protein-bound thyroid hormone and hence jeopardize the commutability of a reference material prepared even from sera that has been subjected to minimal processing (22 ).…”
Section: Preparation Of Samples Intended To Be Commutablementioning
confidence: 99%
“…This protocol has also been validated to be suitable for triglycerides and HDL cholesterol (15 ) and for creatinine (16 ). The C37A protocol has not been validated to produce samples that are commutable with patient samples for other analytes but represents the best available approach and has been used to prepare single-donor serum samples and pools for several investigations of the trueness of measurement procedures for several analytes (17)(18)(19)(20)(21). Thienpont et al found that processing of serum (e.g., sterile filtration, storage before aliquoting and freezing) may disturb the equilibrium between free and protein-bound thyroid hormone and hence jeopardize the commutability of a reference material prepared even from sera that has been subjected to minimal processing (22 ).…”
Section: Preparation Of Samples Intended To Be Commutablementioning
confidence: 99%
“…In conclusion, there are ongoing efforts to harmonise C-peptide immunoassays, including the development of isotope-dilution liquid chromatography-mass spectrometry (LCMS) reference methods [10,11] and a certified reference material [12] for the calibration of these methods, in addition to investigations into the use of panels of serum calibrators for standardisation/harmonisation [13,14]. It is anticipated that the First International Standard will complement these efforts to aid in the standardisation and harmonisation of C-peptide immunoassays.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reason for the low slope observed using serum samples in the comparison between the ARCHITECT and the Elecsys C-Peptide assays cannot be attributed to different standards being used. However, it might be related to different assay formats and the antibodies used (26).…”
Section: Discussionmentioning
confidence: 99%